Analysis of Genetic Diversity Using Different Morphological Characteristics of Seven Dendrobium Orchid Species (Journal of Bio-Science, 2026)
The aim of this study was to bring out the morphological diversity analysis based on the quantitative and qualitative morphological characters of seven species of Dendrobium namely D. aggregatum, D. aphyllum, D. chrysotoxum, D. densiflorum, D. fimbriatum, D. nobile, and D. parishii. The detailed morphological characterization and diversity are discussed and here the vegetative characters revealed variations among the species which can be differentiated from one another. Morphological characterization is an important step which can determine genetic relationships among orchid species in the same genus. Thirty seven characteristics on morphological parameters on the basis of quantitative and qualitative were assayed. There were 30 out of the 37 identified morphological characters (81.08%) that showed diversification in flowers, leaves, pseudobulbs, and roots. From the correlation analysis it was found that 8 out of 10 floral characters have significant positive correlation with themselves at 1% and 5% level. From the principal component analysis (PCA) values, it is exposed that the characters that have a large influence on grouping are the ratio of petal length, lip length and sepal length. The dendrogram topology is supported by the morphological character classification. The dendrogram revealed that D. aphyllum and D. chrysotoxum have the closest kinship between themselves with a similarity coefficient of 2.0 and hence they can be used as parents for cross-breeding and hybridization purpose to obtain new varieties. The results of this study are expected to provide scientific information about genetic diversity among Dendrobium orchid species and to help its conservation efforts in Bangladesh.J. Bio-Sci. 34(1): 51-62, 2026